EVALUASI EFEKTIVITAS PELAYANAN JEMPUT BOLA PENERBITAN AKTA KELAHIRAN DI KABUPATEN BONE STUDI KASUS DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - Ulya Aprillia; Rasyid Thaha; A. Lukman Irwan (Bajang Institute, 2025)
A birth certificate is a legal identity document that must be owned by every person at the time of birth. In an effort to increase birth certificate ownership in Bone Regency, the Population and Civil Registration Office of Bone Regency made an innovative pick-up service to facilitate the community. However, it turns out that this service still has some obstacles. The purpose of this study is to determine the productivity, quality, efficiency, flexibility, and satisfaction of the birth certificate service through the Ball Pickup Service using the theory of effectiveness according to Sumaryadi. This research is a qualitative research using descriptive method with inductive approach. Data collection techniques using observation, interviews and documentation. Meanwhile, data analysis techniques were carried out by reducing data, presenting data and drawing conclusions. From the implementation of this research, it states that the birth certificate service through the ball pick-up program has been carried out well but not maximally. This is due to the lack of understanding and public awareness of the ball pick-up service in the issuance of birth certificates and the lack of facilities and infrastructure that support the implementation of the ball pick-up. Meanwhile, the efforts made are to provide socialization to the Village Government and the community to apply for assistance to the Regional Government to support the birth certificate making service by increasing the number of people who have the right to make a birth certificate